2000
DOI: 10.1212/wnl.54.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of vitamin D related genes in Canadian multiple sclerosis patients

Abstract: The objective of this study was to investigate genes involved in the metabolism and function of vitamin D as candidate genes for genetic susceptibility to MS. Restriction fragment length polymorphisms and highly polymorphic microsatellite markers within or very close to the 1,25(OH)2D3 receptor (VDR) [12q14], the vitamin D binding protein (DBP) [4q12], and the 25(OH)D2 1alpha-hydroxylase [12q13] loci were analyzed for linkage or association with MS. We found no evidence for linkage or association of these cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 5 publications
6
52
2
1
Order By: Relevance
“…Vitamin D-supplemented MS patients experienced, after a period of 1-2 years, less than half the number of exacerbations expected on the basis of their case histories [35]. In a Japanese MS case-control study, an excessive representation of the b allele for the vitamin D receptor gene (OR 2.45; 95% Cl 1.20-5.00) was found among MS patients compared to controls [36], but no evidence for linkage or association of vitamin D receptor gene or other candidate genes for MS was found in a Canadian population [37].…”
Section: Discussionmentioning
confidence: 95%
“…Vitamin D-supplemented MS patients experienced, after a period of 1-2 years, less than half the number of exacerbations expected on the basis of their case histories [35]. In a Japanese MS case-control study, an excessive representation of the b allele for the vitamin D receptor gene (OR 2.45; 95% Cl 1.20-5.00) was found among MS patients compared to controls [36], but no evidence for linkage or association of vitamin D receptor gene or other candidate genes for MS was found in a Canadian population [37].…”
Section: Discussionmentioning
confidence: 95%
“…In another Japanese study, DBP polymorphism showed no differences in distribution between MS patients and non-related healthy individuals (Niino et al, 2002). In a Canadian population, no evidence was found for association or linkage of genes involved in the metabolism and function of vitamin D with MS, including the 1a-OHase gene, the DBP gene, and the VDR gene (Steckley et al, 2000).…”
Section: Ms and Vitamin D-related Genetic Polymorphismmentioning
confidence: 90%
“…Steckely et al 34 found no evidence for linkage or association of VDR [12q14] loci with MS in a Canadian population. Recently, a meta-analysis of VDR polymorphisms and MS showed that ApaI, BsmI, FokI and TaqI VDR polymorphisms are not associated with MS risk.…”
Section: Introductionmentioning
confidence: 99%